Typology of Christian Religious Education in a Pluralistic Indonesian Society in the Era of Globalization - Farida, Muharoma Chomsatul; Sari, Evi Catur (Sekolah Tinggi Teologi Trinity Parapat, 2024)
Globalization has a significant impact on Indonesia's diverse society. Based on these issues, it is necessary to provide relevant Christian religious education considering Indonesia's diverse society. Society tends to become more individualistic and focused on personal needs. Typologies of Christian Religious Education include: first, Bible and Church-centered, second, Theology-centric, third, Ecumenical-Reformative, fourth, Multicultural Christian Religious Education. Multicultural Christian Religious Education is an approach in Christian religious education that emphasizes tolerance, respect, and understanding of cultural diversity, beliefs, and traditions within and outside the Christian community. This research utilizes qualitative methods, through a literature review approach encompassing relevant theories related to the discussed issues. A literature review approach is a type of research conducted by collecting data or scientific literature as the focus of the research, or collecting data in the form of literature, and conducting in-depth analysis of relevant literature to solve a problem.